2007
DOI: 10.1074/jbc.m611031200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB by the Human T Cell Leukemia Virus Type I Tax Oncoprotein Is Associated with Ubiquitin-dependent Relocalization of IκB Kinase

Abstract: Human T cell leukemia virus type 1 (HTLV-1) is the etiological agent of adult T cell leukemia. HTLV-1 encodes a trans-activating protein, Tax, which is largely responsible for the oncogenic properties of the virus. Tax promotes T cell transformation by deregulating the activity of various cellular factors, including the transcription factor NF-B. Tax activates the I B kinase (IKK) via physical interaction with the regulatory subunit, IKK␥, although it is unknown precisely how Tax activates the IKK complex. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
99
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 44 publications
8
99
0
Order By: Relevance
“…CREB activation is required for MTOC/Tax orientation to the cell-cell contact region, but not for Tax/MTOC association (Nejmeddine et al, 2005). That the Tax mutant M47 recruited IKK to the centrosome demonstrates that Tax-induced CREB Harhaj et al (2007), recently reported an association between perinuclear IKK and Tax that colocalize to the Golgi, we documented using complementary approaches that Tax/IKK complexes are associated with the centrosome rather than the Golgi apparatus. Our findings that Tax/IKK interaction occurs in the centrosome, unravel a new function for this cellular organelle.…”
Section: Discussionmentioning
confidence: 69%
“…CREB activation is required for MTOC/Tax orientation to the cell-cell contact region, but not for Tax/MTOC association (Nejmeddine et al, 2005). That the Tax mutant M47 recruited IKK to the centrosome demonstrates that Tax-induced CREB Harhaj et al (2007), recently reported an association between perinuclear IKK and Tax that colocalize to the Golgi, we documented using complementary approaches that Tax/IKK complexes are associated with the centrosome rather than the Golgi apparatus. Our findings that Tax/IKK interaction occurs in the centrosome, unravel a new function for this cellular organelle.…”
Section: Discussionmentioning
confidence: 69%
“…The regulation of Tax subcellular localization and trafficking to different compartments in the cell therefore impinges on the function of Tax (4,38). Recent studies have shown that posttranslational modifications of Tax regulate its function by governing its subcellular localization, stability, and protein-protein interactions (6,20,32). Tax is modified by a number of distinct posttranslational modifications, including ubiquitination, small ubiquitin (Ub)-like modifier sumoylation, phosphorylation, and acetylation (3,6,11,26,27,41), all of which regulate Tax function.…”
mentioning
confidence: 99%
“…Tax has been shown to be both mono-and polyubiquitinated. 36,44,[52][53][54][55] Ubiquitination of Tax is important for both activation of the canonical and noncanonical NF-B pathway and localization to the cytoplasm. 44 Conversely, Tax is also sumoylated, which directs its nuclear localization and is important for both NF-B activation and HTLV-1 LTR activity.…”
Section: Discussionmentioning
confidence: 99%
“…36,53 In the cytoplasm, Tax also concentrates in perinuclear speckles that localize near the centrosome, the microtubule-organizing center, and the cis-Golgi. 54,56,57 Recently, K63-polyubiquitinated Tax was shown to recruit inhibitor B kinase complex to this perinuclear compartment, supporting a model in which Tax activates inhibitor B kinase in a centrosome-dependent manner. 56 However, preliminary data suggest that Tax itself may not need to be ubiquitinated to stabilize the p13 protein.…”
mentioning
confidence: 86%